Keeping secrets from friends: Exploring the effects of friendship quality, loneliness and self-esteem on secrecy. (July 2017) - Corsano, Paola; Musetti, Alessandro; Caricati, Luca; Magnani, Barbara
Abstract: The tendency to keep secrets in adolescents has been studied in particular in their relationships with their parents and associated with psychosocial disadvantages. The current study focused on peer relationships and investigated the effects of friendship quality, loneliness in a multidimensional perspective, and self-esteem on secrecy from friends. Italian adolescents ( N  = 457; 47% male; 100% white) aged between 13 and 19 years ( M  = 16.11; SD  = 1.53) reported their secrecy from friends, peer and parent-related loneliness, aversion and affinity for aloneness, their self-esteem and the quality of their relationships with their friends. The results showed that peer-related loneliness, affinity for aloneness and self-esteem in particular affect keeping secrets from friends, independent of the participant's gender. Moreover, peer-related loneliness and affinity for aloneness mediated the relationship between self-esteem and secrecy. The data were discussed in the light of adolescence developmental tasks.